Relationship Between Risk Factors and The Incidence of Primary and Post-Primary Tuberculosis - Achnes Pangaribuan; Andriyani Risma Sanggul; Agnes Dorothy; Vidi Posdo A. Simarmata; Vanessa Mutiara Marcelina; Febtusia Puspitasari (International Journal of Health and Pharmaceutical (IJHP), 2026)
Tuberculosis (TB) remains a significant global health problem, with Indonesia ranking second in the world for the highest number of cases. This study aims to analyze the relationship between various risk factors and the incidence of primary and post-primary tuberculosis in the Merdeka Public Health Center working area in 2025.Based on preliminary data, there are 122 TB patients in the region diagnosed using the Molecular Rapid Test (TCM). Identified risk factors include host factors such as male gender, productive age (15–64 years), low education, and low economic status. Additionally, home environmental factors play a crucial role in increasing transmission risk, including inadequate residential density (<9m²/person), poor ventilation, lack of natural lighting, and suboptimal air humidity. Negative preventive behaviors and exposure to cigarette smoke are also significant contributors to the incidence of the disease.Mitigation efforts require comprehensive interventions. These must focus not only on medical treatment but also on improving residential environmental conditions and educating the community on healthy behaviors.